National accounting and capital - Hartwick, John M. (Cheltenham, UK ; Northampton, MA, USA : Edward Elgar, 2000)
Presents definitive solutions to current problems in national accounting practice and deals expertly with problems in accounting natural capital, financial capital and skills capital and communicates his solutions in specially designed national accounting tables or matrices.
Includes bibliographical references and index.
oif 30/04/15
Loan
Keywords: National income -- Accounting; Capital